Sonographic diagnosis of osteomyelitis in a dog - Mohamed Shafiuzama; Sindhu G. Nair; C. Ramani; S. Hemalatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Managing infections in fractures treated with open reduction and internal fixation is an ongoing issue in current veterinary orthopaedics. Early diagnosis and treatment improves the prognosis. A 2-year-old male mongrel dog was presented to the Small Animal Orthopaedics Unit of Madras Veterinary College Teaching Veterinary Hospital with a history of non-weight bearing lameness 28 days after open reduction and internal fixation for a simple transverse fracture of distal diaphysis of the left tibia. Ultrasonographic evaluation of the fracture site revealed sub-periosteal fluid collection, intense vascularity and irregular hyperechoic areas at the fracture site whereas the radiograph did not show any significant changes. Follow-up examination after 14 days showed severe periosteal osteolysis under radiography and periosteal fluid collection with infarction at the fracture site under ultrasonography. Based on radiographic and sonographic findings, the case was diagnosed as osteomyelitis.